ASEAN’S RESPONSE THROUGH ASEAN AGREEMENT ON TRANSBOUNDARY HAZE POLLUTION (AATHP) IN TACKLING THE TRANSBOUNDARY HAZE POLLUTIONS ISSUES IN 2015-2019 - Dwiki Zenith Ramadhani (: 2621-0924)
In Southeast Asia, environmental issues become an annual agenda in every regional meeting such as the Transboundary Haze Pollution (THP) issues. The domino effect that resulted from this phenomenon has become increasingly complex, including the degradation of natural resources, health problems for living things, to stretched diplomatic relations between regional countries. ASEAN formulated the Agreement on Transboundary Haze and Pollution (AATHP) as the basic law for addressing this issue since 2003 and has been fully ratified by entire ASEAN member countries in 2015 marked by the ratification of Indonesia as the last ratification among ASEAN membership. This research attempt to explain the phenomenon by utilizing a qualitative method with descriptive analysis to conclude the factors and challenges faced by ASEAN during the implementation of AATHP from 2015 to 2019. Through the approach of regionalism, environmental security, soft law characteristics in international agreements, and fiqh al-biah, this research concluded that the implementation of AATHP is considered to have an insignificant effect in overcoming the transboundary haze issue.Keyword: ASEAN, AATHP, transboundary haze pollution, soft law